George Perkins Marsh : prophet of conservation - Lowenthal, David (Weyerhaeuser environmental book., 2003)
George Perkins Marsh (1801-1882) was the first to reveal the menace of environmental misuse, to explain its causes, and to prescribe reforms. David Lowenthal here offers fresh insights, from new sources, into Marsh's career and shows his relevance today, in a book which has its roots in but wholly supersedes Lowenthal's earlier biography George Perkins Marsh: Versatile Vermonter (1958). Marsh's devotion to the repair of nature, to the concerns of working people, to women's rights, and to historical stewardship resonate more than ever. His Vermont birthplace is now a national park chronicling American conservation, and the crusade he launched is now global. David Lowenthal is professor emeritus of geography at University College London. His books include The Past Is a Foreign Country, West Indian Societies, and The Heritage Crusade and the Spoils of History.